Review of the southern African Leptestheriidae (Branchiopoda: Spinicaudata) I: redescription of Leptestheria brevirostris Barnard, 1924 with comments on diagnostic characters - Rogers, D. Christopher; Tladi, Murphy; Wasserman, Ryan J.; Meyer-Milne, Elizabeth (Zootaxa, 2021)
We present the first records of Leptestheria brevirostris since its discovery in Namibia by Barnard in 1924. Our records come from Botswana and South Africa, and present significant range extensions. We redescribe L. brevirostris according to modern standards and present the first description of the male. We also discovered that L. brevirostris is likely a rock pool specialist, specific to sandstone and gneiss outcrops; this is the first record of a rock pool specialist clam shrimp from Africa and the second rock pool specialist described for Leptestheriidae. Finally, we depict and discuss the validity and usefulness of diagnostic characters for Leptestheria species in southern Africa, especially the usefulness of carapace interval ornamentation.